Ajanta - Mitra, Debala 1925- (New Delhi : Director General, Archaeological Survey of India, 1983)
Description mural paintings in Ajanta Caves, Maharashtra.
Bibliography: p. 80.
Keywords: Buddhist cave temples -- India -- Ajanta; Mural painting and decoration -- India -- Ajanta